2021
DOI: 10.1016/j.puhe.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 morbidity in an ethnic minority: changes during the first year of the pandemic

Abstract: Objectives During the COVID-19 pandemic, ethnic minorities have been more susceptible to infection and demonstrated poorer outcomes. This study describes COVID-19 morbidity and mortality by ethnic group, represented by Arab and Jewish localities in Israel, during the different waves of the outbreak and addresses sociocultural aspects of the pandemic. Study design A retrospective national archive study was conducted in Israel. Methods Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Further, if women are more responsible for grocery shopping than men, as is the case in the United States but has not been measured in Israel [45], they may be less likely to fully adhere to the social-distancing guidelines. Our finding that Jews were more likely to adhere to the guidelines is supported by previous studies that showed a greater toll of the pandemic in the Arabic population of Israel than in the country's Jewish residents [46]. This outcome has been attributed to a myriad of factors, including their lower socio-economic status and education, lower than average trust in the government, unequal distribution of resources within the Israeli society, societal traditions and religious customs, and difficulty in maintaining health behaviors after the initial success of the first lockdown in Israel [46].…”
Section: Discussionsupporting
confidence: 87%
“…Further, if women are more responsible for grocery shopping than men, as is the case in the United States but has not been measured in Israel [45], they may be less likely to fully adhere to the social-distancing guidelines. Our finding that Jews were more likely to adhere to the guidelines is supported by previous studies that showed a greater toll of the pandemic in the Arabic population of Israel than in the country's Jewish residents [46]. This outcome has been attributed to a myriad of factors, including their lower socio-economic status and education, lower than average trust in the government, unequal distribution of resources within the Israeli society, societal traditions and religious customs, and difficulty in maintaining health behaviors after the initial success of the first lockdown in Israel [46].…”
Section: Discussionsupporting
confidence: 87%
“… 2 During the initial waves of the COVID-19 pandemic, ethnic minorities were more susceptible to infection and demonstrated poorer outcomes in terms of morbidity and mortality due to sociocultural aspects of the pandemic; however, this observation was abolished in the later waves. 4 The large global outbreak of SARS-CoV-2 has seriously endangered healthcare systems worldwide. The sudden surge of SARS-CoV-2 has revealed the shortage of critical care medicine resources and intensivists.…”
Section: Reviewmentioning
confidence: 99%
“…Literature about health disparities in Israel includes assessments during the SARS-CoV-2 pandemic and supports several of the aforementioned theories, as we describe henceforth. Arabs living in Israel were found to have higher excess mortality than Jews, which have been linked to adverse health behaviours and health conditions that are more prominent in the Arab population [ 31 ]. These adverse health behaviours include smoking, physical inactivity, and a high fat and refined cereal diet [ 32 ], leading to higher risks of, e.g., diabetes and obesity [ 33 ] and vulnerability for severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%